(untitled) (PIONIR: JURNAL PENDIDIKAN, 2021)
The purpose of this study was to determine the capacity of Biology Education Study Program lecturers in implementing learning management. Research data collection was carried out using survey methods and interviews with students, lecturers and academics at both the Faculty and Institute levels. Sources of data in this study consisted of two, namely: 1). The main data source (primary) is data contained in the Biology Education Study Program, Tarbiyah Faculty, and the Academic Bureau of UIN Ar-Raniry Banda Aceh. 2). Sources of supporting data were obtained from interviews with students and lecturers of the Biology Education Study Program regarding the implementation of learning management at the Biology Education Study Program, Faculty of Tarbiyah and Teacher Training at UIN Ar-Raniry Banda Aceh. Students who were interviewed were taken from representatives of each unit, namely; 5 (five) people for each unit consisting of 2 men and 3 women (5 x 10 units = 50 people) plus a Biology Education Study Program Lecturer who is actively teaching. Data analysis was carried out in two ways, namely quantitative and qualitative analysis. Data processing is done by 1). Quantitative analysis; conducted to see the condition of the capacity of the Biology Education Study Program lecturers in the implementation of learning management with percentage analysis. 2). Descriptive analysis; carried out to provide an accurate and systematic description of the capacity of lecturers in the implementation of learning management in the Biology Education Study Program, Faculty of Tarbiyah and Teacher Training at UIN AR- Raniry. The results showed that the ability of the lecturers of the Biology Education Study Program, Faculty of Tarbiyah and Teacher Training at UIN Ar-Raniry Banda Aceh in the implementation of learning management was classified as good, this was indicated by the average score of the lecturer’s ability, which was 3.48 (classified as good).